Book reviews: The Economics of Imperfect Labor Markets - PAŞNICU, DANIELA (Annals of Spiru Haret University. Economic Series, 2010)
Tito Boeri is professor of economics at Bocconi University in Milan and scientific director at Fondazione Rodolfo Debenedetti. Jan van Ours is professor of economics at Tilburg University in the Netherlands and temporary employee as professor of economics at Melbourne University. Their research field is mainly the labour economics and they have become notorious in the specialist literature for studying relevant economic phenomena, as well as their reflection on every day’s life.